水槽試験・CFD データ統合管理システムの開発 - 和, 中 真之介; 満, 行 泰 河; 稗, 方 和 夫; 大, 和 裕 幸 (日本船舶海洋工学会論文集, 2018)
In this paper, an integrated design database for management of ships' hull information, towing tank test results, and CFD simulation results is developed to support researchers who study to improve CFD technology using tank test and CFD data. To be more concrete, this paper proposes data scheme and develop database system to manage tank test and CFD data by applying metadata description with RDF(Resource description framework), which is usually used for Linked Data. As for the evaluation of the functionalities, the developed management system was applied to management of tank test and CFD data conducted in the University of Tokyo, and it was demonstrated that the data management by metadata can reduce the labor which is required for searching some data. Moreover, by utilizing a system analysis method, it is shown that the developed system's configuration is one of the Pareto optimal configurations under a specific usage context.